2014
DOI: 10.1186/1471-2458-14-686
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle factors and multimorbidity: a cross sectional study

Abstract: BackgroundLifestyle factors have been associated mostly with individual chronic diseases. We investigated the relationship between lifestyle factors (individual and combined) and the co-occurrence of multiple chronic diseases.MethodsCross-sectional analysis of results from the Program of Research on the Evolution of a Cohort Investigating Health System Effects (PRECISE) in Quebec, Canada. Subjects aged 45 years and older. A randomly-selected cohort in the general population recruited by telephone. Multimorbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
201
6
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(234 citation statements)
references
References 28 publications
13
201
6
5
Order By: Relevance
“…A secondary cross-sectional analysis of the PRECISE cohort from Canada did not find a significant association between high risk drinking and multimorbidity (odds ratio (OR) 0.94, 95% CI 0.43-2.03 for men and OR 0.83, 95% CI 0.31-2.23 for women), which is in line with our findings. 9 We found a 32% increase in the multimorbidity hazard in association with physical inactivity. This is consistent with the results of the previous prospective Finnish study which found a 34% increase in the risk of multimorbidity in men and 62% in women with physical inactivity who were initially disease-free.…”
Section: Comparison With Current Literaturementioning
confidence: 56%
See 1 more Smart Citation
“…A secondary cross-sectional analysis of the PRECISE cohort from Canada did not find a significant association between high risk drinking and multimorbidity (odds ratio (OR) 0.94, 95% CI 0.43-2.03 for men and OR 0.83, 95% CI 0.31-2.23 for women), which is in line with our findings. 9 We found a 32% increase in the multimorbidity hazard in association with physical inactivity. This is consistent with the results of the previous prospective Finnish study which found a 34% increase in the risk of multimorbidity in men and 62% in women with physical inactivity who were initially disease-free.…”
Section: Comparison With Current Literaturementioning
confidence: 56%
“…9,10,12 We only included data from the three most recent ELSA waves for this analysis in order to capture all five lifestyle factors; we still had a large number of people in the study with over 100,000 person-months of follow-up, however when assessing different triads and tetrads of unhealthy lifestyle factors the number of people with specific combinations of unhealthy lifestyle factors was quite low as depicted by the small number of people in some triads and tetrads (Supplementary Table 1) and wide confidence intervals of the estimates. Consequently, it is difficult to distinguish true negative findings from the negative findings associated with low statistical power; therefore the findings should be interpreted with caution.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Only a few studies have evaluated the association of modifiable risk factors with multimorbidity, and especially the longitudinal studies are scarce [5][6][7][8][9]. Biological and lifestyle factors such as hypercholesterolemia, hypertension, obesity, smoking, physical inactivity and unhealthy diet are common risk factors for many chronic diseases [1].…”
Section: Introductionmentioning
confidence: 99%
“…19 Recent study found the association of lifestyle factors and multimorbidity. 20 The burden of multimorbidity has typically been studied in high income countries, very few of these studies conducted in low and middle income countries. 4,13 As such, the prevalence and determinants of multimorbidity in Indonesia is relatively unknown.…”
Section: Introductionmentioning
confidence: 99%